Perancangan Aplikasi Time Management Untuk Mahasiswa Berbasis Gamification - Sulistio, Gerry Susanto; Chrisantyo, Lukas; Raharjo, Willy Sudiarto (Fakultas Teknologi Informasi, 2024)
Students commonly encounter challenges in time organization due to assignments and distractions, notably social media. To solve this problem, the application was meticulously crafted employing Design Thinking principles and incorporating gamification elements to bolster student motivation. During the testing phase, Task Scenario was utilized to measure effectiveness, while the System Usability Scale (SUS) was employed to measure user satisfaction. Test results revealed an effectiveness rate of 87,2%, and the SUS yielded an average score of 65.7%. These findings categorize the application within the level D (OK) and high marginal acceptability ranges. It can be inferred that the application still functions normally, and a considerable number of users are able to accept and use it effectively.